Localização de Faltas em Sistemas de Transmissão de Alta Tensão usando ICA - Almeida, Aryfrance Rocha (2007)
Some methods of fault location in transmission lines have been considered in literature, of which we detach the methods based on the crossed correlation, transformed wavelet and the use of neural networks. This work presents an alternative method based upon of independent components analysis (ICA) to localize the distance at which singlephase, two-phase, two-phase grounding and three-phase faults occur in a 500 kV transmission systems starting from different angles of fault incidence at different distances along the line together with fault signals or traveling waves subject to other perturbations unrelated with the desired fault signal at the fault distance placement. Simulations results of a 500 kV high voltage transmission system got with the software Alternative transients program (ATP) show that the proposed methodology implemented with Matlab is a rather efficient tool for various fault types location.